2010
DOI: 10.1007/s11104-010-0585-x
|View full text |Cite
|
Sign up to set email alerts
|

Ancient waste pits with wood ash irreversibly increase crop production in Central Europe

Abstract: During an aerial archeological survey performed in spring 2009, we detected positive cropmarks (increased biomass production) indicating waste pits in the subsoil in a winter wheat (Triticum aestivum L.) stand. Based on pottery samples, the waste pits were dated to the end of the twelfth century or to the first half of the thirteenth century. The aim of this study was to investigate whether there were any differences in the soil chemical properties in arable and subsoil layers between cropmarks and the surroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…In the study site, long-term settlement activities have been documented by large-scale archaeological excavations performed from the 1960s to the 1980s (Pleinerová, Pavlů 1979;Pleinerová 2000). Settlement activities have been linked with the increase in soil pH and concentrations of plant-available P, K, Ca, Mg and Zn in the soil due to the accumulation of wood ash and organic wastes during the life of the settlement (Hejcman et al 2011). Such an increase in nutrient availability can be detected even one thousand years after abandonment of the settlement and might partly explain the high P, Ca and K concentrations recorded in all our study soils.…”
Section: Soil Propertiesmentioning
confidence: 68%
See 1 more Smart Citation
“…In the study site, long-term settlement activities have been documented by large-scale archaeological excavations performed from the 1960s to the 1980s (Pleinerová, Pavlů 1979;Pleinerová 2000). Settlement activities have been linked with the increase in soil pH and concentrations of plant-available P, K, Ca, Mg and Zn in the soil due to the accumulation of wood ash and organic wastes during the life of the settlement (Hejcman et al 2011). Such an increase in nutrient availability can be detected even one thousand years after abandonment of the settlement and might partly explain the high P, Ca and K concentrations recorded in all our study soils.…”
Section: Soil Propertiesmentioning
confidence: 68%
“…Such an increase in nutrient availability can be detected even one thousand years after abandonment of the settlement and might partly explain the high P, Ca and K concentrations recorded in all our study soils. According to our previous experience, Mehlich III P concentrations can range from 100 to 1,300 mg kg -1 in former prehistoric and medieval settlements and the presence of a settlement can be identified according to chemical analyses of contemporary arable soil (Hejcman et al 2011(Hejcman et al , 2013c. The lowest pH being in the grassland soil can be explained by acidification of the upper soil layer by rainwater and by the activity of roots.…”
Section: Soil Propertiesmentioning
confidence: 99%
“…Every farmer thus had the possibility to see positive effects of prehistoric settlement activities on the production of modern crops. Czech lowlands, in contrast to higher altitudes, frequently suffer from moisture shortage during the vegetation season (Trnka et al, 2008;Hlavinka et al, 2009) and the extremely dry spring such as those in 2000 and 2003 were the best for the creation of extremely visible cropmarks. Many new archaeological sites or individual features which had previously not been discovered were identified during those springs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increase in biomass production, positive cropmarks can be identified according to delays in crop ripening, higher concentrations of growth limiting nutrients in the plant biomass (nitrogen (N), phosphorus (P), potassium (K), calcium (Ca) and magnesium (Mg) in particular) and therefore resulting in different colours of stands, an increase in plant height, crop density, more frequent lodging and different shapes and size of crop plants growing above buried archaeological features compared to plants growing in control areas with undisturbed sub-soil (Majer, 1996;Hejcman et al, 2011). Negative cropmarks with markedly reduced crop growth and early crop ripening can be recorded above ancient roads with highly compacted sub-soil layers, and above wall foundations that negative affecting the water and nutrient supply of the crop (Doneus, 2001;Hanson and Oltean, 2003;Lasaponara and Masini, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nutrient-rich patches in the soil profile may also modify the root system because roots are able to proliferate and grow preferentially into nutrient-rich patches (Robinson 1994;Forde & Lorenzo 2001;Hejcman et al 2011). Lucero et al (1999) concluded that water deficit increases the rooting depth of Trifolium repens.…”
Section: Introductionmentioning
confidence: 99%